Sentimentos estressores em estudantes de enfermagem no processo de ensino-aprendizagem utilizando a simulação realística: uma revisão de escopo - Gonçalves, Silvana Aparecida Tasso (2022)
High-fidelity simulation has been increasingly used in nursing education in order to better prepare students for practical activities and internships. However, this educational strategy can cause anxiety and stress in these students during practice, with possible consequences for health and learning. The aim of this study was to understand the occurrence, associated factors and effect on academic performance of the presence of stressful feelings in undergraduate nursing students during realistic high-fidelity simulation. A scope review of the literature was conducted through primary studies in English, Portuguese and Spanish in the following databases: LILACS, SCIELO, PubMED and BDENF. The search was conducted by two researchers, independently, using the descriptors: High fidelity simulation/high fidelity simulation, simulation/simulation, High fidelity/high fidelity, students/students, nursing/nursing, nurse/nurse/nurse, anxiety / anxiety and stress / stress. Publications from the last 10 years were filtered (mixed, quantitative, observational, randomized and pilot study studies). Different instruments were used to measure stressful feelings and most studies pointed to an increase in anxiety and stress during the high-fidelity simulation. Some studies reported that this increase in stressors impaired the final learning performance when at very high levels and that some factors may be associated with high levels of stressors, such as fear of making mistakes, inexperience, demands, among others. It is concluded that high-fidelity simulation, despite being a useful tool for teaching during the nursing course, can result in the emergence of stressful feelings in students during performance. These feelings are associated with several factors and can affect learning during simulation. A better understanding of this phenomenon is important for the planning of realistic simulation activities aiming to maximize its beneficial effect on learning, minimizing any harmful emotional effects